2019
DOI: 10.1002/jcla.23148
|View full text |Cite
|
Sign up to set email alerts
|

Middle‐ and high‐molecular weight adiponectin levels in relation to nonalcoholic fatty liver disease

Abstract: Objective: Adiponectin (APN) circulates as high-molecular weight (HMW), mediummolecular weight (MMW), and low-molecular weight (LMW) forms. Nonalcoholic fatty liver disease (NAFLD) is a common cause of chronic liver disease. Currently, the role of LMW, MMW, and HMW APN remains largely unclear in NAFLD. Methods:We examined the variation of these forms and analyzed the related clinical characteristics in NAFLD. A total of 63 male NAFLD patients (mean age: 43.00 ± 6.10 years) and 70 healthy male subjects (mean ag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 38 publications
0
8
0
Order By: Relevance
“…Although the results of our study do not have clear implications for clinical practice, they may be important for guiding future mechanistic and intervention studies. In fact, the evidence from this and other studies [ 11 16 , 18 ] suggests a possible role of decreased adiponectin levels in the pathophysiology of NAFLD, thus underlining the need for future large-scale studies assessing the predictive as well as the therapeutic role of this adipokine in the spectrum of NAFLD. Additionally, these results may encourage the designing of diagnostic accuracy studies to examine whether plasma adiponectin levels may contribute (alone or in combination with other biomarkers) to the achievement of a non-invasive diagnosis of liver fibrosis.…”
Section: Discussionmentioning
confidence: 75%
See 1 more Smart Citation
“…Although the results of our study do not have clear implications for clinical practice, they may be important for guiding future mechanistic and intervention studies. In fact, the evidence from this and other studies [ 11 16 , 18 ] suggests a possible role of decreased adiponectin levels in the pathophysiology of NAFLD, thus underlining the need for future large-scale studies assessing the predictive as well as the therapeutic role of this adipokine in the spectrum of NAFLD. Additionally, these results may encourage the designing of diagnostic accuracy studies to examine whether plasma adiponectin levels may contribute (alone or in combination with other biomarkers) to the achievement of a non-invasive diagnosis of liver fibrosis.…”
Section: Discussionmentioning
confidence: 75%
“…In recent years, many observational studies [11][12][13][14][15][16] and some meta-analyses [17] have reported that lower plasma adiponectin levels are significantly associated with the presence and severity of NAFLD, especially in patients without T2DM, thereby suggesting that hypoadiponectinemia might represent a risk factor for NAFLD. However, little information is available to date on the association between lower plasma adiponectin levels and the presence of NAFLD or NASH in patients with T2DM [18].…”
Section: Introductionmentioning
confidence: 99%
“…Despite its well-established role in causing insulin resistance, the cause of adipose tissue infl ammation is not currently understood (12). The adiponectin gene was found to be the most abundantly expressed gene in adipose tissue (43). It encodes a 244-amino-acid protein with a predicted size of 30 kDa (8).…”
Section: U N C O R R E C T E Dmentioning
confidence: 99%
“…In patients with NAFLD, low levels of adiponectin are closely associated with the degree of hepatic steatosis, necroinflammation and fibrosis [ 109 , 110 ]. Adiponectin plays an important role in the progression of simple liver steatosis to NASH [ 111 , 112 , 113 , 114 ]. Thus, different studies suggest the use of serum adiponectin levels as a diagnostic measure of the necro-inflammatory grade and fibrosis in NAFLD, as well as it being a potential NAFLD therapeutic target [ 115 ].…”
Section: Adiponectin As a Prognostic Factor In Liver Diseasesmentioning
confidence: 99%